Blood supply planning during natural disasters under uncertainty: a novel bi-objective model and an application for red crescent - Farrokhizadeh, Elmira; Seyfi-Shishavan, Seyed Amin; Satoglu, Sule Itir (Springer Science and Business Media LLC, 2021)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Lagrangian relaxation; blood supply chain; augmented-epsilon constraint method; Discrete location and assignment; Mixed integer programming; disaster; bi-objective model; Multi-objective and goal programming